The impact of digital teaching aids on enhancing early childhood understanding of basic concepts: An integrative model - Susanti, Anita; Rangga Firdaus; Bayu Saputra; Muhammad Nurwahidin; Dina Martha Fitri (Universitas Islam Negeri Raden Intan Lampung, 2026)
Background: Early childhood education faces persistent challenges in delivering abstract foundational concepts through conventional teaching aids that lack interactive and multimodal features. Objective: This study aimed to examine the effect of digital teaching aids within an integrative model on young children's understanding of basic concepts, mediated by cognitive processes including attention, exploration, and schema construction. Methods: A quasi-experimental design with a nonequivalent control group was employed, involving 45 early childhood learners divided into experimental and control groups. Data were analyzed using path analysis to test both direct and indirect effects through mediating cognitive variables. Result: Results revealed a large and statistically significant positive effect of digital teaching aids on conceptual understanding (p < 0.05, effect size > 0.8), with attention, exploration, and schema construction each serving as significant mediators in the learning process. The mediation analysis confirmed that digital tools do not directly enhance understanding alone but operate through structured cognitive pathways. Conclusion: This study contributes an empirically validated integrative model that bridges multimedia learning theory, constructivism, and cognitive load theory, offering practical and policy-relevant guidance for technology integration in early childhood settings.